Kajian Potensi Tumbuhan Nangka (Artocarpus heterophyllus Lam.) dalam Pengobatan Penyakit Infeksi - Helen Anjelina Simanjuntak; Nurbaiti Br. Singarimbun; Defacto Firmawati Zega; Suharni Pintamas Sinaga; Herlina Simanjuntak; Toberni S Situmorang (Herbal Medicine Journal, 2022)
Infectious diseases are one of the health problems because they cause new infectious diseases caused by antibiotic resistance. So it is necessary to search for new antibiotic agents that are sourced from natural ingredients such as jackfruit plants. Jackfruit plant (Artocarpus heterophyllus Lam.) has many benefits ranging from roots, stems, leaves, fruits and seeds. Jackfruit plant has pharmacological properties as anti-inflammatory, antioxidant, antimalarial, antifungal activity, cytotoxic, tyrosinase inhibitory activity and antimicrobial. The purpose of this study was to determine the study of jackfruit plants that have potential as antimicrobials. The research method was carried out using a literature review with online media based on the Web, Scopus, PubMed, Science Direct, ResearchGate, Google Scholar used for publication. The results showed that jackfruit has antimicrobial activity due to the content of bioactive compounds such as: tannins, flavonoids, catechins, artocarpin and artocarpanone. Jackfruit plant parts that have the potential as antimicrobials are the leaves, jackfruit skin, seeds and roots. Jackfruit plants have potential as antimicrobials against Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Propionibacterium acnes, Klebsiella pneumonia, Pseudomonas aeruginosa, Streptococcus mutans, Mycobacterium tuberculosis, Plasmodium falciparum, and Vibrio cholera.